2018
DOI: 10.4314/tjpr.v17i8.15
|View full text |Cite
|
Sign up to set email alerts
|

The antiproliferative and antimicrobial effects of cultivated <i>Anabaena circinalis</i> Rabenhorts ex Bornet and Flahault and <i>Nostoc entophytum</i> Bornet and Flahault

Abstract: diffusion method in order to determine their antimicrobial effects. The anti-cancer activities of these two algae were tested against cancerous cell lines using BrdU cell proliferation ELISA method. The inhibition of these algae ethanol and butanol extracts were tested against Vero and HeLa carcinoma cells in concentrations of 100, 250 and 500 μg/mL. Results: Anabaena circinalis (AC) and Nostoc entophytum (NE) antimicrobial properties against the tes organisms. The buffer extract obtained from AC showed the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…These compounds possess a variety of biological activities and chemical structures, and include cyclic and linear lipopeptides, fatty acids, alkaloids, and other organic chemicals 28. Many reports have mentioned the antibacterial,29 antifungal,30 and cytotoxic31 properties of these compounds. Extract from blue green algae contains several types of biomolecules that can perform reduction and capping reactions in the reduction and the stabilization processes of synthesizing NPs 24,32.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds possess a variety of biological activities and chemical structures, and include cyclic and linear lipopeptides, fatty acids, alkaloids, and other organic chemicals 28. Many reports have mentioned the antibacterial,29 antifungal,30 and cytotoxic31 properties of these compounds. Extract from blue green algae contains several types of biomolecules that can perform reduction and capping reactions in the reduction and the stabilization processes of synthesizing NPs 24,32.…”
Section: Introductionmentioning
confidence: 99%
“…statistical analysis is performed using SPSS software, employing One-way analysis of variance with 95% confidence intervals to identify significant differences among the variables. Means are compared using Tukey's test, and The results are presented graphically 31 .…”
Section: Methodsmentioning
confidence: 99%
“…It can be concluded that Anabaena extract possesses the potential antibacterial substances that can be used against oral pathogens and for dental caries prevention. metabolites have essential properties (Rashad et al, 2018;Yücer et al, 2018;Rashad and El-Chaghaby, 2020). These aquatic microorganisms represent a vast source of metabolites such as alkaloids, carbohydrates, flavanoids, pigments, phenols, saponins, steroids, tannins, terpenes and vitamins (Rashad et al, 2019).…”
mentioning
confidence: 99%